Combined acupuncture and HuangDiSan treatment affects behavior and synaptophysin levels in the hippocampus of senescence-accelerated mouse prone 8 after neural stem cell transplantation - Zhou, Chun-lei (Neural Regen Res, 2018)
Sanjiao acupuncture and HuangDiSan can promote the proliferation, migration and differentiation of exogenous neural stem cells in senescence-accelerated mouse prone 8 (SAMP8) mice and can improve learning and memory impairment and behavioral function in dementia-model mice. Thus, we sought to determine whether Sanjiao acupuncture and HuangDiSan can elevate the effect of neural stem cell transplantation in Alzheimer’s disease model mice. Sanjiao acupuncture was used to stimulate Danzhong (CV17), Zhongwan (CV12), Qihai (CV6), bilateral Xuehai (SP10) and bilateral Zusanli (ST36) 15 days before and after implantation of neural stem cells (5 × 10(5)) into the hippocampal dentate gyrus of SAMP8 mice. Simultaneously, 0.2 mL HuangDiSan, containing Rehmannia Root and Chinese Angelica, was intragastrically administered. Our results demonstrated that compared with mice undergoing neural stem cell transplantation alone, learning ability was significantly improved and synaptophysin mRNA and protein levels were greatly increased in the hippocampus of mice undergoing both Sanjiao acupuncture and intragastric administration of HuangDiSan. We conclude that the combination of Sanjiao acupuncture and HuangDiSan can effectively improve dementia symptoms in mice, and the mechanism of this action might be related to the regulation of synaptophysin expression.